Exploring Campylobacter jejuni: Elucidating pathogenic mechanisms, virulence factors, antimicrobial resistance in diverse animal species - Chinedu Frank Amaeze; Mohammed Dauda Goni; Fadhilah Kamaruzzaman; Gaddafi Mohammed Sani; Aliyu Yakubu (Veterinary Integrative Sciences)
Campylobacter and its species, with a specific reference to Campylobacter jejuni. are zoonotic pathogens known to cause food-borne diseases and are ideally found in humans, poultry, cattle, and even mammals in certain cases. C. jejuni is the predominant foodborne pathogen regularly found in both pets and food animals, posing a significant risk of zoonotic infections to humans and animals alike. Consequently, infections caused by C. jejuni are a substantial concern for global public health, animal welfare, and the food industry. Campylobacter colonizes its host by overcoming stomach acidity, adhering to intestinal epithelial cells using specialized surface structures, and producing virulence factors to establish infection and proliferate within the gastrointestinal tract. Epidemiologically, Campylobacter's transmission dynamics, risk factors, and patterns of infection spread are crucial considerations in understanding and controlling its impact on public health. The global trend of C. jejuni occurrence has significant implications for public health, necessitating heightened surveillance, prevention, and control measures to mitigate the burden of foodborne illness and reduce the associated economic and societal costs. The emergence of Campylobacter strains resistant to multiple antimicrobials poses serious threats to public health, including treatment challenges, increased severity of infections, heightened transmission risk, and potential spread of resistance genes to other bacteria, underscoring the need for enhanced surveillance, antimicrobial stewardship, and research into alternative treatment approaches. Consequently, this review focuses on the intricacies of Campylobacter jejuni with a particular focus on pathogenicity, virulence factors, host specificity, prevalence on different animal models, and antimicrobial resistance including multidrug resistance.